Flipping the classroom: developing teaching skills for future in-service english teachers - Marriott Toledo, Heidi Marlen (2017)
In teaching English as a foreign language (EFL) tofuture in-service teachers, instructors need to develop not just the students’ language proficiency, but also the necessary skills for 21stcentury teaching in the ever changing classroom where pupils are considered as digital natives. The required skills future teachers need to accomplish, a higher level in both the students’ performance and class interest, can be developed through the Flipped classroom model, which is why this research work aims to explore diverse strategies that can be applied to blend theories such as multiple intelligences and higher order thinking in order to develop students’ critical thinking skills through the incorporation of technology outside and inside the classroom. Considerations to differentiated instruction (DI), students’ different levels of Second Language Acquisition (SLA), and the fostering of the Zone of proximal development (ZPD) of learners are also given as a feature that needs to be incorporated in flipped classrooms. In real-to-life teaching practice, this offers students the possibility to incorporate effective practices that can be directly applied in their future classrooms.